The Colorado river delta (Mexico): ecological importance and management - DOI: 10.4025/actascibiolsci.v30i4.5867 - José Luis Fermán Almada; Georges Seingier; María Lourdes Mexicano Vargas; Alejandro García Gastelum; luis Galindo Bect; Concepción Arrdondo Garcia (Acta Scientiarum. Biological Sciences, 2008)
The Colorado river delta is a unique coastal system in the world, as it combines two important systems: the Colorado river and the Gulf of California. Consequently, the delta is dominated by bilateral interests, and influenced by administrative, political and natural processes, which involve the countries of the United States and Mexico. Located in the northern part of the Gulf of California, under a condition of natural isolation, a series of environmental attributes have been developed (biotic and abiotic) that are only observed in is region. In this work, the development of the bilateral political relations and the most important ecological characteristics are presented, as well as the management instruments that have been developed for over 80 years. From these issues, the possible scenario for the region is defined, and the development of methodologies for monitoring the effects of these possible tendencies on the natural components of the delta is proposed.